The Effect of Multiple Role Conflict and Social Support on Organizational Commitment in Career Women in Medan - T. Elfira Rahmayati; Khairunnida Khairunnida (Budapest International Research and Critics University, 2020)
This study aims to determine the effect of multiple role conflict and social support on organizational commitment. The population of this study is a married career woman in Medan. By using purposive sampling method with a sample of 300 people. Data were collected using a questionnaire that has been tested for validity and reliability. The data analysis technique used multiple regressions. The results of this study indicate that there is a negative effect of multiple role conflict on organizational commitment with the regression coefficient having a value of -0.210, there is effect of social support on organizational commitment with a value of 0.000 < 0.005 and the regression coefficient has a value of 0.396 and there is an effect of multiple role conflict and support social simultaneously with the regression coefficient value has a value of 0.280 or 28%.